Hardware Development of Dual-Modality Tomography Using Electrical Resistance and Ultrasonic Transmission Tomography for Imaging Liquid and Gas - Fazlul Rahman, Mohd Yunus; Suzanna, Ridzuan Aw; Ruzairi, Abdul Rahim; Leow, Pei Ling; Mohd Hafiz, Fazalul Rahiman; Yasmin, Abdul Wahab; Nor Muzakir, Nor Ayob; Shahrulnizahani, Mohammad Din; Puspanathan, Jaysuman (Springer, 2022)
In decades, single-modality technique focuses on particular application such as liquid/gas, gas/solid, liquid/liquid and liquid/solid which has drawbacks in imaging complex flow with multiple components. This paper focuses on the development of dual-modality tomography system (DMT) integrating ultrasonic tomography and electrical resistance tomography (ERT) to visualize cross-sectional images of two-phase liquid/gas in vertical column. A combination of soft-field and hard-field tomography system measures different physical parameters of two-phase liquid/gas specific of two different material properties which are conductivity (σ) and acoustics impedance (Z). A DMT system is developed with 16 units of ultrasonic transceiver sensors, and 16 units of ERT electrode positioned alternately on a single-plane arrangement to perform measurement simultaneously. The reconstructed tomographic images obtained from measurement data from these two modalities are then fused into a single tomographic image by employing discrete wavelet transform (DWT).